Penerapan Sanksi Pelanggaran Awig-Awig Terhadap Krama Banjar Tegeha Desa Adat Sempidi - Kadek Yogi Pranata Mulyawan A; I Nyoman Putu Budiartha; I Ketut Sukadana (Jurnal Interpretasi Hukum, 2022)
Awig-awig is a rule set by village adat or krama Banjar Adat, which is used as a guideline in carrying out Tri Hita Karana in accordance with Mascara village and French religion in adat/banjar villages with the same reaction by adat. Continue to learn the concept of Tri Hita Karana in such a way that breaking the front hand will cause a major imbalance or harmonization of the summary and will also be punished according to the agreement of the hand. On that basis, the problem posed in this thesis is how to apply the awig awig punishment in the Banjar traditional village of Tegeha Sempidi to the residents of Banjarese manners who violate the rules and elements of Banjar manners. / violators of ethics. The research method used is experimental legal research with a community approach and direct field work. The results of this study, enforcement of sanctions is carried out because Paruman is led by Kelian and Banjar Prajuru and is supported by all krama banjara who follow Paruman and its prohibition elements. cheat by reducing the size of rice.